Meningkatkan Minat Remaja dalam Mengkuti Kajian Majelis Ta’lim Melalui Sosialisasi Keagamaan - Iim Siti Masitoh; Rika Purnamasari; Usep Kurniawan (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
The background of this research is that nowadays social relations among teenagers are increasingly wider and tend to be free. So it is not uncommon for teenagers to fall into bad relationships. The Ta'lim Baiturrahmah Council has quite a large congregation who attend regular recitations every week, and many teenagers are involved, both as listeners and those who participate in helping with activities at the Baiturrahmah Ta'lim Council. The aim of this research is to find out how to increase teenagers' interest in participating in studies at the Baiturrahmah Ta'lim Council. The research method used is PAR. location observation, FGD to determine the theme and time of implementation, coordination with partners and owners of the ta'lim assembly to obtain permission, KPM technical preparation, religious outreach activities to increase youth interest. The results obtained from this research are ways to increase teenagers' interest in participating in studies at the Baiturrahmah Ta'lim Council by becoming a place to gain knowledge, a place for teenagers to get good advice, a place to build friendships, a place to instill noble morals, and become a place to fill teenagers' free time with positive activities.